Genomic Plasticity Enables Phenotypic Variation of Pseudomonas syringae pv. tomato DC3000 - Bao, Zhongmeng; Stodghill, Paul V.; Myers, Christopher R.; Lam, Hanh; Wei, Hai-Lei; Chakravarthy, Suma; Kvitko, Brian H.; Collmer, Alan; Cartinhour, Samuel W.; Schweitzer, Peter; Swingle, Bryan (PLOS ONE, 2014)
Whole genome sequencing revealed the presence of a genomic anomaly in the region of 4.7 to 4.9 Mb of the Pseudomonas syringae pv. tomato (Pst) DC3000 genome. The average read depth coverage of Pst DC3000 whole genome sequencing results suggested that a 165 kb segment of the chromosome had doubled in copy number. Further analysis confirmed the 165 kb duplication and that the two copies were arranged as a direct tandem repeat. Examination of the corresponding locus in Pst NCPPB1106, the parent strain of Pst DC3000, suggested that the 165 kb duplication most likely formed after the two strains diverged via transposition of an ISPsy5 insertion sequence (IS) followed by unequal crossing over between ISPsy5 elements at each end of the duplicated region. Deletion of one copy of the 165 kb region demonstrated that the duplication facilitated enhanced growth in some culture conditions, but did not affect pathogenic growth in host tomato plants. These types of chromosomal structures are predicted to be unstable and we have observed resolution of the 165 kb duplication to single copy and its subsequent re-duplication. These data demonstrate the role of IS elements in recombination events that facilitate genomic reorganization in P. syringae.